2003
DOI: 10.1111/j.1749-6632.2003.tb03216.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and Morphological Integration of Neural Progenitor Cells Transplanted into the Developing Mammalian Eye

Abstract: Transplantation of neural stem/progenitor cells has been proposed as a novel approach for the replacement and repair of damaged CNS tissues. We have evaluated the influence of the host cellular microenvironment upon the survival, differentiation, and integration of neural progenitor cells transplanted into the CNS. Using this approach, we have investigated the fate of neural progenitor cells in vivo following transplantation into the developing mammalian eye. Murine brain progenitor cells (mBPCs) isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 25 publications
0
37
1
1
Order By: Relevance
“…Differentiation in the primary cultures was associated with realization of the genetically determined cell potentials intrinsic of the native tissues. Despite some experimental data indicate integration of the cerebral progenitor cells into the retina [22], we think that, due to specifi c features of differentiation of these cells, only the neurotrophic effect of heterotopically transplanted progenitor cells of the brain on the retina is possible. The prospects of this approach are confi rmed by experimental animal studies [13].…”
Section: D)mentioning
confidence: 87%
See 1 more Smart Citation
“…Differentiation in the primary cultures was associated with realization of the genetically determined cell potentials intrinsic of the native tissues. Despite some experimental data indicate integration of the cerebral progenitor cells into the retina [22], we think that, due to specifi c features of differentiation of these cells, only the neurotrophic effect of heterotopically transplanted progenitor cells of the brain on the retina is possible. The prospects of this approach are confi rmed by experimental animal studies [13].…”
Section: D)mentioning
confidence: 87%
“…Methods of growing and culturing of SPC originating from human fetal brain were recently developed [6]. Cultured human cells from the presumptive cortex after transplantation into the brain, spinal cord, or retina caused sig nifi cant recovery of functions, which was shown on various models of neurodegenerative diseases in experimental animals [1,3,7,13,22]. For realization of specifi c potential in cell therapy, neural SPC during culturing should express transcription factors regulating their proper development and differentiation.…”
mentioning
confidence: 99%
“…As a potential approach for treating retinal disease, neural progenitor cells (NPCs) have been proposed as a unique source of transplantable cells to replace lost cells in the damaged eye. Various NPC types have been transplanted into the retina including retinal progenitor cells (RPCs) [1,2] brain progenitor cells (BPCs) [3][4][5], adult hippocampal progenitor cells (AHPCs) [6][7][8], and iris-derived/ciliary body cells [9][10][11]. Although transplantation of different progenitor cell types has been variably successful, retinal and ciliary body derived cells have shown the most promise.…”
Section: Introduction Bmentioning
confidence: 99%
“…Both of the cell populations chosen have been transplanted into developing and degenerate retinal environments [1,[3][4][5][12][13][14][15]. Characterizing the molecular differences between these cells using a proteomics approach is important because different populations of progenitor cells display differential differentiation, integration, and migration after transplantation.…”
Section: Introduction Bmentioning
confidence: 99%
“…It was shown that RPCs can be isolated from pre-natal or few days post-natal mouse [14], rat [15] and human [16,17] retinas and can be cultured in vitro. Although there is a great difference between in vivo and in vitro stem cell differentiation and survival [18], the knowledge obtained from in vitro experiments will be necessary for the development of new in vivo assays and new therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%